Kajian Pencemaran dan Strategi Pengelolaan Lingkungan Di Kawasan Pelelangan Ikan (TPI) Pulau Baai Kota Bengkulu - Risna Armalia; Didi Ardiyansyah; Radeni Ilyan Putra; Reflis Reflis; Satria P Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The Fish Auction Site (TPI) of Pulau Baai in Bengkulu City plays a significant economic and social role, yet it faces substantial environmental pressures due to intense human activities. This study aims to identify the types of environmental pollution based on affected media (water, soil, and air), and to formulate sustainable environmental management strategies. A descriptive analysis method was employed, utilizing field observations and literature review. The findings reveal that water pollution originates from organic and domestic waste from fish processing and port activities; soil pollution is caused by the accumulation of solid waste and chemical seepage; and air pollution stems from gaseous emissions due to organic matter decomposition. These pollution forms lead to the degradation of water quality, contamination of coastal soil, public health risks, and threats to the sustainability of fisheries resources. Based on the findings, recommended strategies include spatial planning, development of waste treatment facilities, regulatory enforcement, and community education. This study is expected to serve as a reference for environmental policy development in coastal fishery areas in Bengkulu City.